MARTABAT MANUSIA DALAM PERSPEKTIF ISLAM - Rafly Prahmana Hidayat; Zaini Dahlan, Hadi Lapian Pohan, Taufik Hidayat (CV. ADIBA AISHA AMIRA, 2024)
The concept of dignity is the fundamental basis for all human rights and is the basic basis and value inherent in every individual. While it cannot be denied that this concept is a topic of controversy among experts in various circles it is important to analyze the basic principles that guide this process. Some scholars argue that the concept of human dignity which is considered vital in Islam is wrong. On the other hand, there are also those who reject the existence of human dignity. Controversy among Muslim scholars has permeated discussions regarding the basic principles of Islam. This article aims to analyze contested features of intrinsic human dignity in human rights discourse and Islamic literature. The first part of the study explores the notion of dignity inherent in international and regional human rights instruments. The next part of this dissertation will discuss the meaning of human dignity as outlined in the declaration of human rights in Islam. The third part will specifically examine the meaning of dignity originating from the Al-Quran and other sources of Islamic jurisprudence. In the end, this research concludes that the study of the theoretical foundations of human dignity in Islamic thought will make a real contribution to the development of universal human rights norms and the growth of basic human rights standards in the Islamic world.